2016
DOI: 10.1002/2015wr017650
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tillage on macropore flow and phosphorus transport to tile drains

Abstract: Elevated phosphorus (P) concentrations in subsurface drainage water are thought to be the result of P bypassing the soil matrix via macropore flow. The objectives of this study were to quantify event water delivery to tile drains via macropore flow paths during storm events and to determine the effect of tillage practices on event water and P delivery to tiles. Tile discharge, total dissolved P (DP) and total P (TP) concentrations, and stable oxygen and deuterium isotopic signatures were measured from two adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
154
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(175 citation statements)
references
References 43 publications
(72 reference statements)
9
154
0
Order By: Relevance
“…Understanding the factors that affect surface–tile connectivity may help identify regions and/or conditions that promote P losses via tile drainage, as there is substantial evidence that runoff is rapidly routed from the surface into tile drains through macropores (King et al, 2015b; Kleinman et al, 2015b; Williams et al, 2016). Further, a comprehensive understanding of site‐specific or climate factors that influence rapid surface–tile connectivity may improve modeling efforts, which currently do not capture such processes effectively (Radcliffe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the factors that affect surface–tile connectivity may help identify regions and/or conditions that promote P losses via tile drainage, as there is substantial evidence that runoff is rapidly routed from the surface into tile drains through macropores (King et al, 2015b; Kleinman et al, 2015b; Williams et al, 2016). Further, a comprehensive understanding of site‐specific or climate factors that influence rapid surface–tile connectivity may improve modeling efforts, which currently do not capture such processes effectively (Radcliffe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Preferential flow might be enhanced by reduced tillage. In comparison with the tilled systems, the no-tilled systems showed an increase in P loss loads (Djodjic et al 2002) and led to relatively higher concentrations of dissolved P in drainage water (Williams et al 2016). Therefore, the reduced soil tillage systems without ploughing that have been applied since 2006 might be associated with the decreasing CAL-soluble P in the topsoil of the experiment presented here.…”
Section: Discussionmentioning
confidence: 99%
“…2B). Previous studies even showed that vertical macropores allow new water to be translocated from the surface to tile drains (e.g., Stamm et al, 1998;Smith et al, 2015;Williams et al, 2016). In the current study, however, dye stains did not extend to the 100-cm depth where tiles are typically installed in the region.…”
Section: Discussionmentioning
confidence: 99%